STRATEGI MEMPERSIAPKAN SUMBER DAYA INSANI PADA MAHASISWA UNTUK BERWIRAUSAHA DAN BISNIS SYARIAH - Lely Shavira; Tasya Rachma; Muhammad Rizki Atipanudin; Mega Oktaviany (Taksasila Edukasi Insani, 2023)
The number of graduates and diplomas is not comparable to the available jobs. This reality should be an incentive for the younger generation, especially students, to start entrepreneurship. With entrepreneurship, the chances of creating jobs will be greater, so the number of unemployed in Indonesia will decrease little by little. Furthermore, this study aims to provide knowledge to students who want to enter the world of business about how to prepare themselves and their human resources so as to be able to survive in the hard business world when they also remain active in following lectures. The study uses descriptive qualitative research to describe strategies and advice for students who want to start their careers in entrepreneurship. Based on the results of the research, it is known that the strategy for preparing human resources for students who want to balance themselves in doing business and also remain active in the classroom can be done by applying some very important attitudes, namely having a high work ethic, managing time carefully, always introspecting themselves, building networks, always praying and being grateful, and always being proud and committed.